2011
DOI: 10.1007/s11999-011-1818-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Glass 13-93 as a Subchondral Substrate for Tissue-engineered Osteochondral Constructs: A Pilot Study

Abstract: Background Replacement of diseased areas of the joint with tissue-engineered osteochondral grafts has shown potential in the treatment of osteoarthritis. Bioactive glasses are candidates for the osseous analog of these grafts. Questions/purposes (1) Does Bioactive Glass 13-93 (BG 13-93) as a subchondral substrate improve collagen and glycosaminoglycan production in a tissue-engineered cartilage layer? (2) Does BG 13-93 as a culture medium supplement increase the collagen and glycosaminoglycan production and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In vivo , increased angiogenesis was found around subcutaneous implants of 13–93 B3 glass, and studies reported high levels of collagen and connective tissue remodeling around the glass . This report is supported in vitro by production of collagen I and IV and glycosaminoglycans into subchondral bioactive glass implants for potential use in osteochondral defects . Further clinical investigation of borate glass (13‐93 B3) for use in long‐term, non‐healing wounds showed a significant decrease in wound size within 1–3 months of treatment and return of sensation to the scar area .…”
Section: Introductionmentioning
confidence: 51%
“…In vivo , increased angiogenesis was found around subcutaneous implants of 13–93 B3 glass, and studies reported high levels of collagen and connective tissue remodeling around the glass . This report is supported in vitro by production of collagen I and IV and glycosaminoglycans into subchondral bioactive glass implants for potential use in osteochondral defects . Further clinical investigation of borate glass (13‐93 B3) for use in long‐term, non‐healing wounds showed a significant decrease in wound size within 1–3 months of treatment and return of sensation to the scar area .…”
Section: Introductionmentioning
confidence: 51%
“…When co-cultured with bovine chondrocyte-seeded agarose hydrogels, porous scaffolds of a silicate 13–93 bioactive glass served as a medium supplement for culturing tissue-engineered cartilage in vitro [155,156]. Constructs were cultured in serum-free, chemically defined medium supplemented with TGF-β 3 (10 ng ml −1 for the first 14 days of culture) [157].…”
Section: Bioactive Glasses In Chondrogenesis and Osteochondral Tismentioning
confidence: 99%
“…12d), which means that mechanical properties can be lower than might be expected; for example, the 45S5 glass-ceramic foams had a compressive strength of 0.4 MPa (90% porosity). However, by choosing an optimal polymer foam and by optimizing the amount of glass particles (<10 lm) used in the slurry (35 vol.%), compressive strengths of 11 MPa were obtained with 13-93 scaffolds, with 85% porosity and pore sizes ranging from 100 to 500 lm [173].…”
Section: Melt-derived Bioactive Glass Scaffoldsmentioning
confidence: 99%